A Standardized Multimodal Neurological Monitoring Protocol-Guided Cerebral Protection Therapy for Venoarterial Extracorporeal Membrane Oxygenation Supported Patients - Shi, Xiaobei; Gu, Qiao; Li, Yiwei; Diao, Mengyuan; Wen, Xin; Hu, Wei; Xi, Shaosong (Frontiers in Medicine, 2022)
Background: The main objective of this study was to investigate the role of a multimodal neural monitoring (MNM)-guided protocol in the precision identification of neural impairment and long-term neurological outcomes in veno-arterial extracorporeal membrane oxygenation (V-A ECMO) supported patients. Methods: We performed a cohort study examining adult patients who underwent V-A ECMO support in our center between February 2010 and April 2021. These patients were retrospectively assigned to the “with MNM group” and the “without MNM group” based on the presence or absence of MNM-guided precision management. The differences in ECMO-related characteristics, evaluation indicators (precision, sensitivity, and specificity) of the MNM-guided protocol, and long-term outcomes of surviving patients were measured and compared between the two groups. Results: A total of 63 patients with V-A ECMO support were retrospectively assigned to the without MNM group (n=35) and the with MNM group (n=28). The incidence of neural impairment in the without MNM group was significantly higher than that in the with MNM group (82.1% vs. 54.3%). The MNM group exhibited older median ages (52.5 [39.5, 65.3] vs. 31 [26.5, 48.0], P=0.008), a higher success rate of ECMO weaning (92.8% vs. 71.4), and a lower median duration of building ECMO (40.0 [35.0, 52.0] vs. 58.0 [48.0, 76.0]) and median ECMO duration days (5.0 [4.0, 6.2] vs. 7.0 [5.0, 10.5]) than the group without MNM. The MNM-guided protocol exhibited a higher precision rate (82.1% vs. 60.0%), sensitivity (95.7% vs. 78.9%), and specificity (83.3% vs. 37.5%) in identifying neural impairment in V-A ECMO support patients. There were significant differences between the two groups in the long-term outcomes of survivors after discharge for 1, 3 and 6 months (P < 0.05). Conclusion: The MNM-guided protocol is conducive to precision management in V-A ECMO supported patients and can significantly increase the precision of identifying neural impairment and improve long-term neurological outcomes.